The Power of Representation : Publics, Peasants, and Islam in Egypt. - Gasper, Michael (Stanford University Press, 2008)
Traces the links between the development of modern Egyptian identity and the burgeoning Islamic modernist movement from the mid-1870s until the 1910s.